The Effect of Human Resources Quality and Work Professionalism on Employee Performance Mediated by Organizational Commitment - Lering, Leonardus Frediyanto Moat; Suwitho, Suwitho; Suhermin, Suhermin (UNIVERSITAS PAKUAN, 2023)
The purpose of this study was to test and analyze the effect of human resource quality and work professionalism on employee performance mediated by organizational commitment at KSP. Kopdit Obor Mas. This type of research is quantitative research. The sample used in this study were permanent employees of KSP. Kopdit Obor Mas which amounted to 179 people. The data source used is a primary data source where the data collection technique is through distributing questionnaires to employees who are the sample of this study. Testing is done starting with testing the research instrument, namely the validity test and reliability test. Data analysis using multiple linear regression analysis and path analysis. The results of this study indicate that partially Human Resource Quality, work professionalism and organizational commitment have a significant effect on employee performance. The results of path analysis show that organizational commitment can mediate the effect of human resource quality and work professionalism on employee performance. This means that organizational commitment can be a mediator between the quality of human resources and work professionalism with employee performance.